Exploring the Impact of Exclusive Breastfeeding and Complementary Feeding on Pediatric Feeding and Swallowing - Putri, Anggi Resina; Susanti, Nadya (Poltekkes Kemenkes Surakarta, 2025)
Background: A child’s eating and swallowing abilities depend on physiological readiness, environmental stimulation, and early feeding experiences. Lack of exclusive breastfeeding or inappropriate complementary feeding can hinder oromotor development, leading to difficulties in chewing, swallowing, or self-feeding during the preschool years. This study examines the relationship between exclusive breastfeeding history, complementary feeding practices, and toddlers’ eating and swallowing abilities. Methods: This cross-sectional study was conducted in Surakarta, Central Java, from April to August 2025, involving 50 randomly selected participants. The dependent variables were children’s swallowing and eating abilities, while the independent variables included exclusive breastfeeding history and complementary feeding practices. Data were gathered using a structured questionnaire and analyzed through path analysis using Stata version 13. Results: Optimal eating ability was significantly influenced by a history of exclusive breastfeeding (b = 2.05; p = 0.048), appropriate complementary feeding (b = 2.50; p = 0.022), and adequate swallowing ability (b = 2.36; p = 0.030). Exclusive breastfeeding and proper complementary feeding also indirectly improved eating ability through their positive effects on swallowing ability. Conclusion: This study highlights the need for maternal education on exclusive breastfeeding and appropriate complementary feeding to promote optimal eating and swallowing development in toddlers, thereby minimizing the risk of related disorders and their potential impact on nutrition and growth.